BopN is a Gatekeeper of the Bordetella Type III Secretion System - Navarrete, Kevin Munoz; Bumba, Ladislav; Prudnikova, Tatyana; Malcova, Ivana; Allsop, Tania Romero; Sebo, Peter; Kamanova, Jana (Microbiology spectrum, 2023)
The classical Bordetella species infect the respiratory tract of mammals. While B. bronchiseptica causes rather chronic respiratory infections in a variety of mammals, the human-adapted species B. pertussis and B. parapertussisHU cause an acute respiratory disease known as whooping cough or pertussis. The virulence factors include a type III secretion system (T3SS) that translocates effectors BteA and BopN into host cells. However, the regulatory mechanisms underlying the secretion and translocation activity of T3SS in bordetellae are largely unknown. We have solved the crystal structure of BopN of B. pertussis and show that it is similar to the structures of gatekeepers that control access to the T3SS channel from the bacterial cytoplasm. We further found that BopN accumulates at the cell periphery at physiological concentrations of calcium ions (2 mM) that inhibit the secretion of BteA and BopN. Deletion of the bopN gene in B. bronchiseptica increased secretion of the BteA effector into calcium-rich medium but had no effect on secretion of the T3SS translocon components BopD and BopB. Moreover, the ΔbopN mutant secreted approximately 10-fold higher amounts of BteA into the medium of infected cells than the wild-type bacteria, but it translocated lower amounts of BteA into the host cell cytoplasm. These data demonstrate that BopN is a Bordetella T3SS gatekeeper required for regulated and targeted translocation of the BteA effector through the T3SS injectisome into host cells. IMPORTANCE The T3SS is utilized by many Gram-negative bacteria to deliver effector proteins from bacterial cytosol directly into infected host cell cytoplasm in a regulated and targeted manner. Pathogenic bordetellae use the T3SS to inject the BteA and BopN proteins into infected cells and upregulate the production of the anti-inflammatory cytokine interleukin-10 (IL-10) to evade host immunity. Previous studies proposed that BopN acted as an effector in host cells. In this study, we report that BopN is a T3SS gatekeeper that regulates the secretion and translocation activity of Bordetella T3SS.
Keywords: Whooping Cough; Calcium; Mammals; gatekeeper; Virulence Factors; Bacterial Proteins; vápník; type III secretion system; Bordetella; faktory virulence; BopN; Bordetella pertussis; savci; Animals; lidé; Type III Secretion Systems; Humans; zvířata; bakteriální proteiny; sekreční systém typu III; pertuse